Levels of bisphenol-A in different paper products in Guangzhou, China, and assessment of human exposure via dermal contact. Issue 3 (11th February 2015) - Fan, Ruifang; Zeng, Biyan; Liu, Xiaosu; Chen, Chao; Zhuang, Qinwei; Wang, Yongjun; Hu, Mingli; Lv, Yanshan; Li, Junnan; Zhou, Yuanxiu; Lin, Zhi Yuan William
Abstract : Bisphenol A (BPA) is a chemical widely used both in plastics production as a food and beverage container and in thermal papers as a color developer. Abstract : Bisphenol A (BPA) is a chemical widely used both in plastics production as a food and beverage container and in thermal papers as a color developer. Dietary consumption is the main route of human exposure to BPA, but dermal absorption through handling different papers might be underestimated or ignored. In this study, BPA in different paper products, including different types of papers, receipts and Chinese currencies, were investigated. BPA was detected in receipts ( n = 87) and Chinese currencies ( n = 46) with concentrations of 0.17–2.675 × 10 4 μg per g paper and 0.09–288.55 μg per g paper, respectively. Except for parchment papers ( n = 3), copy papers ( n = 3) and food contact papers ( n = 3), BPA was measured in all of the other paper products, with levels of 0.01–6.67 μg per g paper. BPA transferred from thermal papers to common papers increased with the increasing contact pressure. Compared with that in water, the migration speed of BPA was doubled in the synthetic sweat. Washing hands could reduce BPA dermal exposure, and washing hands with lotion was the most efficient way. However, about 19–47% of BPA was still found on hands after different washing methods. Dermal absorption via handling of receipts and papers was estimated to be 36.45 ng per day for the general population and 1.54 × 10 −3 to 248.73 μg per day for a cashier. These values are below the maximum doses recommended by the U.S. Environmental Protection Agency and the European Food Safety Authority. However, due to its uncertain adverse effects on human beings, long-term BPA exposure through dermal absorption should be paid more attention, particularly for some occupational populations.